A Holistic Investigation of Terahertz Propagation and Channel Modeling toward Vertical Heterogeneous Networks - Tekbiyik, Kursat; Ekti, Ali Riza; Kurt, Gunes Karabulut; Gorcin, Ali; Yanikomeroglu, Halim (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
User-centric and low-latency communications can be enabled not only by small cells but also through ubiquitous connectivity. Recently, the vertical heterogeneous network (V-HetNet) architecture has been proposed to backhaul/fronthaul a large number of small cells. Like an orchestra, the V-HetNet is a polyphony of different communication ensembles, including geostationary Earth orbit and low Earth orbit satellites (e.g., CubeSats), and networked flying platforms along with terrestrial communication links. In this study, we propose terahertz (THz) communications to enable the elements of V-HetNets to function in harmony. As THz links offer large bandwidth, leading to ultra-high data rates, it is suitable for backhauling and fronthauling small cells. Furthermore, THz communications can support numerous applications from inter-satellite links to in-vivo nanonetworks. However, to savor this harmony, we need accurate channel models. In this article, the insights obtained through our measurement campaigns are highlighted to reveal the true potential of THz communications in V-HetNets.
Keywords: Antennas; Wireless communication; 6G mobile communication; Low earth orbit satellites; CubeSat; Quality of service; MILLIMETER; COMMUNICATION; Engineering; Telecommunications